Short-term postoperative outcomes of lymphadenectomy for cholangiocarcinoma, hepatocellular carcinoma and colorectal liver metastases in the modern era of liver surgery: insights from the StuDoQ|Liver registry - Knitter, Sebastian; Raschzok, Nathanael; Hillebrandt, Karl Herbert; Benzing, Christian; Moosburner, Simon; Nevermann, Nora; Haber, Philipp; Gül-Klein, Safak; Fehrenbach, Uli; Lurje, Georg; Schöning, Wenzel; Fangmann, Josef; et al. (European journal of surgical oncology, 2024)
Introduction - The clinical role of lymphadenectomy (LAD) as part of hepatic resection for malignancies of the liver remains unclear. In this study, we aimed to report on the use cases and postoperative outcomes of liver resection and simultaneous LAD for hepatic malignancies (HM). - Materials and methods - Clinicopathological data from patients who underwent surgery at 13 German centers from 2017 to 2022 (n = 3456) was extracted from the StuDoQ|Liver registry of the German Society of General and Visceral Surgery. Propensity-score matching (PSM) was performed to account for the extent of liver resection and patient demographics. - Results - LAD was performed in 545 (16%) cases. The most common indication for LAD was cholangiocarcinoma (CCA), followed by colorectal liver metastases (CRLM) and hepatocellular carcinoma (HCC). N+ status was found in 7 (8%), 59 (35%), and 56 cases (35%) for HCC, CCA, and CRLM, respectively (p < 0.001). The LAD rate was highest for robotic-assisted resections (28%) followed by open (26%) and laparoscopic resections (13%), whereas the number of resected lymph nodes was equivalent between the techniques (p = 0.303). LAD was associated with an increased risk of liver-specific postoperative complications, especially for patients with HCC. - Conclusion - In this multicenter registry study, LAD was found to be associated with an increased risk of liver-specific complications. The highest rate of LAD was observed among robotic liver resections.